Contributions of native plants to the urban ecosystem: Bursa (Turkey) sample: Native plants in urban ecosystem - Ender Altay, Elvan; Zencirkıran, Murat (TeMA - Journal of Land Use, Mobility and Environment, 2024)
For the coming years, it is a potential danger that the ecosystems existing in urban areas will be heavily affected, especially under the pressure of climate change. In the face of this danger, a good understanding of the natural landscape in urban areas and the adoption of local species are of great importance for sustainability. Native plants contribute to the life of their communities by easily adapting to the environmental conditions in their areas. In this study, the contributions of 72 native woody taxa to the ecosystem were investigated in Bursa (Turkey), which has a rich flora. The relationships that emerged in terms of the criteria examined revealed important results. The existence of a positive relationship between the criteria found in the study shows that the use of native plants is important for the protection of the ecosystem in urban areas. The main purpose is to examine the ecological needs of native plants and their contribution to the urban ecology to determine whether the existing correlation relationships are meaningful. It is aimed to associate natural areas in cities with the ecological needs of plants.